Gradski predjel „Na Andriji” u povijesnoj jezgri Dubrovnika : prostorni razvoj i urbanistička obilježja - Laznibat, Zehra (Array, 2018)
This paper is the first complete and systematic study on the spatial and historical development of the urban area Na Andriji in the historic core of Dubrovnik. The history of the monastic complexes of St Andrew and St Mark between the 13th and the 17th century serves as a basis for analysis of their urban setting and structure, subdivision of land, streets and dominant buildings and their effects on the urban fabric. The research results are used in the preservation and revitalization of archaeological heritage.